The Federal Income Tax Effects of the Missouri Version of the Uniform Divorce Act - Alan Gunn (Washington University Law Quarterly, 1974)
The marital property provisions of the new Missouri divorce law render the tax treatment of property transfers and alimony payments unclear. As to property transfers, the problem is that the new law appears to give the wife an interest in property that previously would have been regarded as belonging to the husband. Since this is so, it is possible to argue that a “transfer” of appreciated property to the wife is part of a “division” of property between “co-owners,” and therefore not taxable. Although transfers of appreciated property in connection with a divorce are usually taxable, divisions of community property (and, probably, other jointly owned property) are not. As to alimony, the problem is that payments satisfying the formal requirements of section 71 of the Internal Revenue Code have sometimes been held not to qualify for taxation as alimony because they were intended as payments for the wife’s property. Because they give the wife an interest in property that would otherwise be solely her husband’s, the marital property provisons can be used to challenge the tax status of purported alimony payments, at least in cases where the husband receives the bulk of the marital property and the divorce decree or settlement agreement is ambiguous.
Keywords: Alimony and maintenance; Divorce and separation; Income tax -- Individual -- United States; Settlements